ChemInform Abstract: Fe(DS)3, an Efficient Lewis Acid — Surfactant Combined Catalyst (LASC) for the One‐Pot Synthesis of Chromeno[4, 3‐b]chromene Derivatives by Assembling the Basic Building Blocks. Issue 38 (30th August 2013) - Pradhan, Koyel; Paul, Sanjay; Das, Asish R.
Abstract The use of ferric dodecylsulfate renders possible a three‐component heteroannulation for the synthesis of the title compounds in water.